TINJAUAN AL-QUR’AN TERHADAP KESETARAAN GENDER DALAM PEMBAGIAN WARISAN (STUDI ANALISIS PADA SURAH AL-NISA AYAT 11) - Ruslan, Muhammad (AR ROSYAD: Jurnal Keislaman dan Sosial Humaniora, 2023)
The Problems among the people never stop at one time. Eventhough these problems have been raised by the scholars of the Salaf. Just like a few years ago there was a lot of talk about the difference in the heritage provisions of 2/1 for boys and girls which was considered unfair by feminists. Starting from this problem, the author took the initiative to thoroughly discuss how according to the Qur'an, and whether the 2/1 distribution can be said to be fair. The focus and purpose of this research is to find out the Qur'anic perspective on gender equality in heritage distribution, and to find out the forms of justice for gender equality in inheritance distribution. The type of research used in this study is included in content analysis with a library research approach. The result of this study indicate that: The distribution of inheritance determined by the Qur'an in surah al-Nisa' Verse 11 (Li al-dzakari mitslu hadd al-untsayain) for sons and daughters includes a distribution that is not equal because the distribution the heritage listed in Nisa surah Verse 11 (Li al-dzakari mitslu hadd al-untsayain) sons get a 2/1 share or in other words boys get twice the share of girls. The fair distribution of 2/1 is due to several things, including the burden on sons is greater and sons are obliged to provide their wealth to their family